Work Engagement as a Mediator of the Connection between Compensation and Employee Competence: Evidence from Nigeria - Isah, Sani; Ibrahim, Rashidah Mohammad; Karim, Fazida; Gwadabe, Uzairu Muhammad (Journal of Social Economics Research, 2022)
Competence is as an essential attribute of employees which describes their work ability, attitude, knowledge and skills. This study aims to explore whether work engagement as a mediator can influence the link between compensation and employee competence and also establish the nexus between the two variables within the context of Nigeria’s Universal Basic Education System Administration (UBESA). Studies that explore the impact of compensation on employee competence and the mechanism through which it influences employee competence appears to be scarce. The study used a quantitative approach to collect data from 341 randomly selected respondents. The instruments include the Utrecht Work Engagement Scale, Compensation Scale and Competency Scale and were adapted from prior studies to suit the current study. SPSS Amos 24 was used to analyze the data. The results revealed that compensation has a significant influence on employee competence and that work engagement mediates the connection between compensation and employee competence. This study contributes theoretically by proposing a new model that examines the mediating effect of work engagement on compensation and employee competence. The findings provide a better insight for the management of Nigeria’s UBESA on how to increase employee competence. Finally, the study offers suggestions for future research.